Hepatosplenic tuberculosis simulating secondary malignant lesions with cholangitis. (December 2016) - Diallo, Ibrahima; Mbengue, Ababacar; Gning, Sara; Amar, Mouhamed; Ndiaye, Bineta; Diop, Yankhoba; Fall, Fatou; MBaye, Papa
Abstract Background Hepatic and/or splenic tuberculosis may simulate much pathology including malignancies, which can roam the diagnosis. Biopsy is necessary for diagnosis. The treatment allows healing and a cleaning of radiological lesions. Case presentation We report a case of a 48-old-black Senegalese woman, immunocompetent, hospitalized for febrile jaundice and poor general condition. Imaging and hepatic biopsy showed hepatosplenic tuberculosis with cholangitis, simulating secondary malignancies lesions. The outcome was favorable under treatment. Conclusion In front of hepatic nodular lesions simulating malignancies in a tuberculosis endemic areas, achieving a liver biopsy helps rectify the diagnosis.